Team Problem-Solving with Agile Business Process to Improve Employee Performance Using NVIVO Analysis at PT XYZ - Kuswanto, Arif; Qonita, Abida (Journal of Advances in Accounting, Economics, and Management, 2024)
To achieve optimal performance, telecommunications companies, particularly PT XYZ, which are closely aligned with technological advancements, must develop strategic frameworks to address evolving market demands and sustain their operational viability. PT XYZ faces several collaboration-related challenges, including iterative redundancies, insufficient project transparency, inadequate cross-functional communication, and ineffective inter-departmental coordination. To address these issues and enhance organizational performance, PT XYZ has adopted Agile Ways of Working. This qualitative study aims to examine employee behavior at PT XYZ in relation to their experiences with the transition to Agile Ways of Working. The research involved interviewing six informants with relevant roles and experience in the Agile transformation, conducted online and recorded for data collection. The interview data were subsequently analyzed using NVIVO 12 Pro software. The findings suggest that for effective implementation of Agile Ways of Working, organizations must first identify and understand the challenges they will encounter in order to devise appropriate solutions. It is crucial to invest in employee competency development through targeted training and workshops and to support these initiatives with company policies that align with agile principles. PT XYZ utilize the Scrum Framework due to its rapid adaptability to change. The implementation of Agile Ways of Working at PT XYZ has been assessed as effective, enhancing collaboration, streamlining communication between individuals and departments, and proving suitable for application within the telecommunications sector.